Pengaruh Profitabilitas dan Kepemilikan Institusional terhadap Tax Avoidance dengan Komisaris Independen sebagai Variabel Moderasi - Salsa Fitri Yanti; Rahmat Mulyana Dali; Rasiman Rasiman (Institut Nalanda, 2026)
This study aims to examine the effect of profitability and institutional ownership on tax avoidance, with independent commissioners serving as a moderating variable. The object of this research consists of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique used in this study was purposive sampling, resulting in 16 companies with a total of 80 observation units over five years. The data analysis method employed was panel data regression analysis using the Common Effect Model (CEM) as the best model and the Estimated Generalized Least Square (EGLS) estimation technique with the assistance of EViews 13 software. The results of the study provide empirical evidence that profitability and institutional ownership partially have a negative effect on tax avoidance. Furthermore, independent commissioners are proven to moderate the relationship between profitability and tax avoidance, as well as the relationship between institutional ownership and tax avoidance. These findings indicate that independent commissioners play an important role in strengthening both internal and external supervision in order to balance profit optimization with corporate tax compliance in tax avoidance practices influenced by profitability and institutional ownership. The presence of independent commissioners can encourage companies to implement more transparent and accountable governance practices, thereby reducing aggressive tax avoidance behavior. In addition, effective oversight by independent commissioners may improve the credibility of financial reporting and ensure that corporate decisions remain aligned with applicable taxation regulations and the interests of stakeholders.